2020
DOI: 10.1111/ijcp.13933
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown, Social Media exposure regarding COVID‐19 and the relation with self‐assessment depression and anxiety. Is the medical staff different?

Abstract: Introduction Locking the humanity in their homes, COVID‐19 forced people to use the technology at hand to keep informed about the outbreak and to keep close to their loved ones. During this time, even if physical health is theoretically unaffected, keeping calm and sane can be challenging. The aim of this research was to evaluate whether exposure to COVID‐19 information available in the digital space has a different impact on the mental condition of Romanian medical staff, compared with the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…Moreover, about 40% of the respondents obtained their information from social media channels. Unlike most published studies on a similar theme, one study showed that, for Romanian people, the exposure to COVID-19 information through social media was not related to self-assessed anxiety or depression [21].…”
Section: Perspectives On Covid-19 Prevention and Knowledgecontrasting
confidence: 60%
“…Moreover, about 40% of the respondents obtained their information from social media channels. Unlike most published studies on a similar theme, one study showed that, for Romanian people, the exposure to COVID-19 information through social media was not related to self-assessed anxiety or depression [21].…”
Section: Perspectives On Covid-19 Prevention and Knowledgecontrasting
confidence: 60%
“…36,37 However, consistent with the findings of other studies regarding judging the validity of information on social media platforms, the Saudi Arabian general population are more likely to judge the validity of information based on their own experience, and deem it beneficial for the public to share COVID-19 related information sans evidence. 10,[16][17][18][19][20][21] Thus, it can be posited that Saudi Arabian general population's perception of COVID-19 related information circulating on social media platforms is of a neutral disposition. While the Saudi Arabian general are less likely to contribute and share medical information with others, and are less likely to share the information without first confirming that it is correct, there are still a small portion of Saudi Arabians who deem it okay to share any COVID-19 related information on social media platforms.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 A large body of literature support that the general population are willing to share information on social media sans evidence. 10,[16][17][18][19][20][21] Previous studies investigate the effect of the recirculation of misinformation during COVID-19 which for example, the abuse and misuse of chlorine to wrongfully prevent against COVID-19. 3 Among natural remedies, herbal remedies was one of the rumors which was highly recirculated on social media and on different platforms, as well as having published research articles, from the idea that natural remedies would be harmless and its use would be without side effects [22][23][24] .While herbal remedies and herbal products are not discouraged to be taken, they should not be considered a sole cure for COVID-19, as the management of COVID-19 does not exist, except for reducing the chances of transmission through vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Our studied population is the university students in Malaysia who had to study off-campus (online) due to the pandemic-related lockdown. Being locked down and studying off-campus had exposed students to different social circumstances from when they were studying on campus [29], because they had limited access to their social environment and developed higher reliance on social media [30], [31]. Furthermore, because as mentioned in the sociometer theory [24], individuals assess themselves based on the social feedback they retrieve, the lockdown situation drove our population to rely heavily on the feedback from social media to evaluate themselves [32], [33].…”
Section: Introductionmentioning
confidence: 99%